AB1048 Does chondrocalcinosis associate with a different radiographic phenotype of osteoarthritis?. (23rd January 2014) - Abhishek, A.; Doherty, S.; Maciewicz, R.; Muir, K.; Zhang, W.; Doherty, M.
Abstract : Background: Some studies suggest that the structural changes in joints with osteoarthritis (OA) and co-existing radiographic chondrocalcinosis (CC) are distinct from joints with OA alone. However, other studies suggest that there is no such difference. To date, the radiographic phenotype of OA associated with CC has not been examined in a large study. Objectives: To ascertain if the radiographic phenotype of OA with co-existent CC is distinct from that of OA alone. Methods: A case-control study embedded in GOAL – the Genetics of Osteoarthritis and Lifestyle study (n=3, 170). All participants have radiographs of knees, hands, and pelvis which have been scored for structural changes of OA, and for the presence of CC. Cases had OA and CC at a particular joint, and controls had OA without CC at the same joint (joint based analysis). OA was defined as Kellgren and Lawrence score ≥2 at hip, ≥3 at knee, and definite joint space narrowing (JSN) at wrist or MCPJs. Osteophyte score and JSN score were summated at each joint, and converted to tertiles. Cysts, subchondral sclerosis, and attrition were scored present or absent. Each structural radiographic change was compared between cases and controls. Odds ratio (OR) and 95% confidence interval (CI) was used to measure the association. The OR was adjusted for age, gender, and body mass index. If CC associated with an OA phenotype at one joint, the association between this phenotype and CC at distant joints was examined. Results: In radiographic knee OA, knee CC associated with attrition at both knees (aOR (95%CI) 2.33 (1.24-4.34) right, and 2.55 (2.37-4.76) left knee) but did not associate with any other radiographic structural change. In radiographic hip OA, hip CC associated with less osteophytosis at both hips, mild JSN and sclerosis at right but not left hip, and did not associate with cysts. In wrist OA, wrist CC associated with subchondral sclerosis at the right (aOR (95%CI) 2.09 (1.03-4.22)) but not the left wrist (aOR (95%CI) (1.75 (0.86-3.55)). In those with scapho-trapezioid joint (STJ) OA, wrist CC associated with sclerosis bilaterally (aOR (95%CI) 3.53 (1.06-11.75) right, and 3.61 (1.26-10.37) left STJ). In MCPJ OA, wrist CC associated with more cysts in the right (aOR (95%CI) 2.16 (1.10-4.21)) but not in the left hand (1.49 (0.56-4.03)), while in 1st CMCJ OA wrist CC associated with more cysts in the left (aOR (95%CI) 2.20 (1.31-3.71)) and possibly also in the right hand (aOR (95%CI) 1.69 (0.95-3.03)). In wrist, 1st CMCJ, STJ, and MCPJ OA there was no association between wrist CC and any other structural radiographic change. CC at distant joints associated with attrition at both knees (aOR (95%CI) 2.27 (1.16-4.36) right, and 2.21 (1.12-4.29) left knee), but did not associate with any other structural change where local effects were present. Conclusions: Our findings suggest that joints with OA and co-existent CC have a different radiographic phenotype from OA alone, and that this radiographic phenotype is joint specific. For example, knees with OA + CC (both local or distant) are more likely to have attrition, while hips with OA + CC have milder OA phenotype. Similarly, MCPJ or 1st CMCJ OA + wrist CC may have more cysts while wrists and STJs with OA + wrist CC are more likely to have sclerosis. Thus CC seems to modify the bone remodelling in OA and this impact is joint specific. Disclosure of Interest: None Declared.